APLIKASI PEMBELAJARAN DASAR BAHASA INGGRIS UNTUK ANAK DENGAN METODE PQRST BERBASIS MULTIMEDIA MOBILE - Yus Jayusman; Faiqunisa Faiqunisa; Reni Triastuti (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2019)
English was introduced early on because the children have learned the so-called golden age of brilliant, which allows children at an early age learn languages quickly. Found those things need to be built upon an application which is expected to be used by parents and children, the method used to build these applications is the PQRST IE Preview, Question, Read, Summarize, pronunciation of vocabulary Test in the form of pictures and voice, learning and practice.